Formulation and characterization of noodles from black rice (Oryza sativa) flour. - Naquita, Olive Grace Baldemor
Formulation and characterization of fresh noodles with black rice (Oryza sativa) was made. Black rice was utilized in a form of flour and substituted to the normal plain noodles. The formulation of fresh noodles with black rice flour and control were the following: Formulation 1 (30% black rice flour), Formulation 2 (50% black rice flour), Formulation 3 (70% black rice flour) and Control (100% white rice flour). Formulation C was determined as the most preferred formulation (MPF) of fresh noodles with black rice flour and was perceived as like moderately during the consumer testing. Sensory analyses resulted to a dark gray color (4.0), very smooth mouthfeel (3.0), and firm texture (3.0). The proximate analysis showed that the noodles with black rice flour had a moisture content of 46.68%, 4.75% crude fat, 3.52% crude fiber, 0.35% crude ash, 5.86% crude protein, and 38.85% carbohydrates. The product had a pH value of 6.715 and aw equivalent to 0.9781. The product was noted to have higher moisture content, crude protein, crude fiber, and ash content. The moisture content, crude fiber, crude protein, and ash content of the product were statistically higher than the control (rice noodles utilizing white rice flour) except for the amount of crude fiber and carbohydrates. The results that were analyzed using two-sample T-test showed no significant difference for moisture content, crude fat, crude protein, ash content, and carbohydrates except for the crude fiber analysis. The result of the consumer test for 100 respondents showed that 43% rated the black noodles as ?like moderately?, 30% rated the product as ?like very much?, 19% rated the product as ?like extremely?, 6% rated it as ?like slightly?, 2% rated it as ?neither like nor dislike?, and both 0% rated it as ?dislike slightly? or ?dislike? Based on the results, black rice flour can be a good alternative in the production of fresh noodles.